The Role of the Wordwall Interactive Learning Tool in Enhancing the Spatial Thinking Skills of 10th-Grade Students at SMA Negeri 5 Palu - Rachmah, Salbiyah; Hasan, Haslita Rahmawati; Suwarni, Suwarni; Arsy, Risma Fadhila; Novianti, Iis (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2026)
The study aimed to examine the effectiveness of interactive Wordwall media in improving the spatial thinking skills of Grade X students at SMA Negeri 5 Palu. A quantitative approach employing a pre-experimental one-group pretest-posttest design was adopted. The participants consisted of 32 Grade X students selected through purposive sampling. Data were collected using a spatial thinking test administered before and after the intervention and supported by student and teacher response questionnaires. The data were analyzed using descriptive statistics and Normalized Gain (N-Gain) analysis. The findings revealed a substantial improvement in students' spatial thinking skills, as indicated by an increase in the mean score from 51.88 in the pretest to 94.69 in the posttest. The average N-Gain score reached 0.910, indicating a high level of learning improvement with an effectiveness percentage of 90.99%. Students also expressed highly positive perceptions toward the implementation of Wordwall (86.17%), while the teacher provided a moderate evaluation (43.28%), highlighting the importance of technological infrastructure and instructional readiness for successful implementation. These findings demonstrate that interactive Wordwall media effectively supports the development of students' spatial thinking skills by promoting active engagement, immediate feedback, and meaningful interaction with spatial concepts. This study contributes empirical evidence supporting the integration of interactive digital media as a pedagogical strategy for strengthening spatial thinking in geography education.